A Critical Analysis of Malang City Government Policy on Road Repair Targets: An Evaluation of Infrastructure Performance Based on Dunn’s Model - Ardik, Muhammad (PANGRIPTA, 2025)
This study examines the implementation of the Malang City Government’s policy targeting the repair of damaged and potholed roads. Employing a qualitative approach and guided by William N. Dunn’s evaluation model, the research assesses the policy along six key indicators: effectiveness, efficiency, sufficiency, equity, responsiveness, and timeliness. Data were gathered through in-depth interviews with municipal staff and document analysis. Findings indicate that while the policy has achieved high levels of road quality—with 98.85% of roads meeting a “sound” condition—the distribution of repair efforts remains uneven. Key impediments include budget constraints, weather-related delays, and limited technical human resources, whereas strong community participation and continuous monitoring emerge as central supporting factors. The study concludes with recommendations for enhanced data integration, adaptive budget planning, and strengthened public engagement to further optimize infrastructure repair efforts in Malang City.